SURPLUS FREE CASH FLOW, KOMITE AUDIT, DAN MANAJEMEN LABA (Students' Journal of Accounting and Banking, 2013)
This study aimed to examine the effect of surplus free cash flow and audit committees on earnings management. Earnings management is proxied by discretionary accruals estimated by the model Jones. The population in this study is a manufacturing company listed on the Indonesian Stock Exchange (BEI) in 2008-2011. Based on purposive sampling method, the number of samples in this study of 27 companies and the number of observations were 108 observational studies. Testing this hypothesis using multiple linear regression analysis. The results of this study indicate that the Surplus Free Cash Flow has a negative and significant effect. Audit Committee has a positive and significant effect on earnings management.Keywords: Earnings management, Surplus Free Cash Flow, Audit Committees.